Electrochemically Stimulated DNA Release from a Polymer-Brush Modified Electrode - Sempionatto, Juliane R. [UNESP]; Gamella, Maria; Guz, Nataliia; Pingarrón, José M.; Pedrosa, Valber A. [UNESP]; Minko, Sergiy; Katz, Evgeny (Wiley, 2015)
Single-stranded DNA molecules were loaded on the mixed poly(2-vinylpyridine) (P2VP)/polyacrylic acid (PAA) brush covalently attached to an indium tin oxide (ITO) electrode. The DNA deposition was performed at pH3.0 when the polymer brush is positively charged due to protonation of pyridine groups in P2VP, thus resulting in electrostatic binding of the negatively charged DNA. By applying electrolysis at -1.0V (vs. Ag/AgCl reference) oxygen reduction resulted in the consumption of hydrogen ions and local pH increase in the vicinity of the electrode surface. The process resulted in the local pH ca. 7.5 which yielded the negative state of the mixed polymer-brush due to dissociation of carboxylic groups of PAA. This resulted in the electrostatic repulsion and release of the loaded DNA. The developed approach allows cyclic load-release of the DNA with the significantly increased amount of the released DNA comparing with previously reported systems. Further options for the improvements of the system are discussed.
Keywords: DNA release; Electrochemical signal; Modified electrode; PH change; Polymer brush